Protocolos de seguridad y su incidencia en la higiene - Vivas Lucas, Maoly (2021)
This case study is focused on the safety and hygiene protocols of the students of the Juan Montalvo educational unit of Canton Baba, this study was carried out through the descriptive method which allows identifying the factors, characteristics and aspects that intervene in the In addition to collecting the data and the results obtained, it was possible to determine the incidence of safety and hygiene protocols in the students, the deductive method was also used, allowing the information obtained through research carried out to be analyzed, where it has the the presence of the quality of the educational unit, students and teachers, through instrument techniques, facilitates the collection of information to have an approach to the problem of the educational unit Juan Montalvo of Canton Baba. Surveys were applied to 25 students of said institution in order to know the incidence of them, protocols and student hygiene. Safety protocols are a useful tool for the protection of the student, enabling them to take care of the same in occasions where it is required: hygiene in the student and within the institution must be ordered in order to take care of the environment that surrounds them having everything in order for the improvement of the classrooms.